Membangun Transparansi Pengadaan Barang Dan Jasa Melalui Peningkatan Peran Ict Dalam Mereduksi Korupsi - Nayabarani, Sabrina Dyah (UI Scholars Hub, 2017)
Corruption in goods and services procurement is one of the most frequent corruption in Indonesia. So, this article discuss about the role of information communication and technology (ICT) and its mechanism for improving transparency as an effort to prevent corruption. This study apply descriptive method, literature review, and analysis the research which have been done by preceding researcher. This article conclude that ICT is statistically significant for reducing corruption, but the implementation of that system should be needed further evaluation. There are some important things which need more evaluation, such as: sufficiency of skilled worker for operating e-procurement, user support, stakeholders involvement, ICT infrastructure, institutional setting, and social community background.